2006
DOI: 10.1080/03014460600707503
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity, rickets and long-bone growth in post-medieval Britain—a cross-population analysis

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 32 publications
4
57
3
Order By: Relevance
“…ANCOVA allows for the detection of differences between the regression slopes of two datasets, while acknowledging the influence of dental age as a covariate (Pinhasi et al, 2006). This method was only applied to individuals between 0 and 12 years of age to avoid the complications of the sex‐differentiated pubertal growth spurt, and to allow for comparison with the data from a modern sample for TR diameter (see below).…”
Section: Methodsmentioning
confidence: 99%
“…ANCOVA allows for the detection of differences between the regression slopes of two datasets, while acknowledging the influence of dental age as a covariate (Pinhasi et al, 2006). This method was only applied to individuals between 0 and 12 years of age to avoid the complications of the sex‐differentiated pubertal growth spurt, and to allow for comparison with the data from a modern sample for TR diameter (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Although we acknowledge weaknesses in the work, we, nevertheless, believe that this result is discouraging for those who would monitor the health effects of more subtle geographical or temporal differences in lifestyles using endochondral growth in skeletal remains. A number of authors (e.g., Mays, 1985Mays, , 1995Mays, , 1999Lewis, 2002a,b;Pinhasi et al, 2006) have demonstrated that a more complete insight into child health can be obtained if growth studies are combined with markers of disease or nonspecific stress. Combining study of endochondral growth with markers of growth arrest such as Harris lines can lead to insights into the occurrence or otherwise of catch-up growth following episodes of growth arrest.…”
Section: Discussionmentioning
confidence: 98%
“…However, samples of the disease diagnosed as osteomalacia can be found dating from as far back as ancient Egypt (Nerlich et al, 2002) to a few cases of this type described in modern time series (Brickley et al, 2005). Cases of rickets are known from sites dating back to the period of Roman influences (Blondiaux et al, 2002;Schamall et al, 2003), but are more frequently reported from sites dating back to the Middle Ages (Ortner & Mays, 1998;Pinhasi, 2006) and modern times (Mays et al, 2006(Mays et al, , 2007. Gładykowska-Rzeczycka (2001) has described 25 cases of rickets dating back from the Neolithic, medieval and modern times found on the territorial lands of Poland.…”
Section: Introductionmentioning
confidence: 96%